2013
DOI: 10.1194/jlr.d031112
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the phospholipase activity of endothelial lipase in mouse plasma

Abstract: This article is available online at http://www.jlr.orgIn evaluating plasma EL function, measurement of EL enzymatic activity is more informative than quantifi cation of EL concentration by immunoassay because the latter does not differentiate between active noncovalent homodimer and inactive monomer ( 15 ), active full-length enzyme and inactive proteolytically cleaved enzyme ( 16,17 ), and the presence or absence of the endogenous plasma inhibitor of EL,18 ).Since the discovery of EL in 1999 ( 19, 20 ), subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The present study successfully established a direct method for assessing the plasma human EL-specific phospholipase activity using a combination of IP and a fluorogenic phospholipid substrate. The principle of this assay has recently been reported and validated for the measurement of the murine plasma EL activity 25) . In the present study, furthermore, we depleted native IgG using pretreatment of plasma samples with Protein A prior to EL-IP, as plasma is abundant in native IgG and may interfere with the IP process.…”
Section: Discussionmentioning
confidence: 99%
“…The present study successfully established a direct method for assessing the plasma human EL-specific phospholipase activity using a combination of IP and a fluorogenic phospholipid substrate. The principle of this assay has recently been reported and validated for the measurement of the murine plasma EL activity 25) . In the present study, furthermore, we depleted native IgG using pretreatment of plasma samples with Protein A prior to EL-IP, as plasma is abundant in native IgG and may interfere with the IP process.…”
Section: Discussionmentioning
confidence: 99%
“…EL activity assays-Phospholipase activity was monitored using the EnzChek Phospholipase A1 assay kit (ThermoFisher) as described previously (26). EL (final concentration of ~10 ÎŒg/ml) and ANGPTL proteins (final concentrations: 0-4000 ng/ml ANGPTL3; 0-210 ng/ml ANGPTL8) were combined and incubated at 37°C (or at 4°C or 22°C for temperature studies) for 30 minutes (unless otherwise indicated).…”
Section: Production Of Endothelial Lipase and Lipoprotein Lipase Conditioned Media-to Produce Elmentioning
confidence: 99%
“…To directly assess the EL-specific activity in Fur-hKO plasma versus that in WT plasma, we used a commercially available fluorogenic substrate and a neutralizing mouse EL antibody to measure specifically the EL activity as recently reported (42). The phospholipase activity was determined in pre-and postheparin plasma from WT and Fur-hKO mice of 2 months of age, in the presence or absence of a mouse EL antibody (Fig.…”
Section: Circulating Cholesterol and Cholesterol Profiles In Hkomentioning
confidence: 99%